1985
DOI: 10.1136/adc.60.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen breath test in schoolchildren.

Abstract: The frequency of a false negative hydrogen breath test was higher than previously reported, but this does not affect the superiority of this method of testing over the conventional blood glucose determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
4

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
1
15
0
4
Order By: Relevance
“…No entanto, há autores que demonstram uma proporção de até 9,2% de crianças colonizadas por flora incapaz de produzir hidrogênio 27 .…”
Section: Discussionunclassified
“…No entanto, há autores que demonstram uma proporção de até 9,2% de crianças colonizadas por flora incapaz de produzir hidrogênio 27 .…”
Section: Discussionunclassified
“…1, Table 1). They probably lacked the appropriate colonic flora to produce hydrogen, either idiopathically (20, 21) or because of previous use of antibiotics (22). In Lesotho primary LM starts to appear around the age of two years (7), which coincides with the age when breast feeding is traditionally stopped.…”
Section: Discussionmentioning
confidence: 99%
“…Breath hydrogen responses show a great deal of individual variation, likely generated by factors such as variation in intestinal microflora and intestinal transit times in individuals. Additionally, there can be false‐negative test results in hydrogen nonproducers, which has been shown to occur in around 10–13% of healthy and symptomatic children . It has also been reported that the children who showed symptoms of diarrhea after consuming fruit juice had the highest breath hydrogen levels .…”
Section: Breath Hydrogen Testing Principles and Parametersmentioning
confidence: 99%